If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5(x + -6) = 48 Reorder the terms: 3 + -5(-6 + x) = 48 3 + (-6 * -5 + x * -5) = 48 3 + (30 + -5x) = 48 Combine like terms: 3 + 30 = 33 33 + -5x = 48 Solving 33 + -5x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + -5x = 48 + -33 Combine like terms: 33 + -33 = 0 0 + -5x = 48 + -33 -5x = 48 + -33 Combine like terms: 48 + -33 = 15 -5x = 15 Divide each side by '-5'. x = -3 Simplifying x = -3
| 31/5+b=4/5 | | 4(t+20)=1/5(20t+400) | | 4(x-2)=4x+2 | | 3(x-1)=2(x+8) | | 9x-11=-20 | | -2x+2=-14+6x | | x-3=x-6 | | 3n+40+2n=15 | | 4x+2y+18=0 | | -8x-14=-134 | | -12x=4y-16 | | 1.11=x+3x | | 5x+7(x-1)=-3x | | -1+2x=x-7 | | 2+5=210 | | x-2y-6=10 | | 3x+7-(x+2)=-36 | | 5/17=p/16 | | -1/6+n=1/6 | | -5(6-2n)=45-2n | | logx-log(x-5)=2 | | x-3cosx=0 | | 96=-8(n-8) | | 30x+25y=275 | | cosx-3sinx=2 | | 5/9*p=-10 | | -3x+1=4x-34 | | 5x+4(5x+3)=-13 | | -96=-8(n-8) | | 9x+6=-201 | | S(n+6)=-5n | | 7x-2+2x+1=17 |